2014
DOI: 10.1097/mnm.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin suppresses background intestinal 18F-FDG uptake on PET/CT scans

Abstract: This pilot study shows that treatment with rifaximin for 2 days before PET/CT scanning can significantly reduce physiological F-FDG uptake in the normal colonic lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Rifaximin was reported to prevent stress-induced mucosal inflammation, intestinal barrier impairment, and visceral hyperalgesia, which was linked to enhanced gut permeability. It is possible that contrary to previous suggestions [ 4 ], suppressed intestinal FDG activity by rifaximin might be due to improved intestinal permeability rather than a bactericidal effect.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Rifaximin was reported to prevent stress-induced mucosal inflammation, intestinal barrier impairment, and visceral hyperalgesia, which was linked to enhanced gut permeability. It is possible that contrary to previous suggestions [ 4 ], suppressed intestinal FDG activity by rifaximin might be due to improved intestinal permeability rather than a bactericidal effect.…”
Section: Discussioncontrasting
confidence: 86%
“…A previously mentioned study [ 4 ] demonstrated suppressed bowel FDG uptake by Rifaximin and showed that bacteria are responsible for the retention of FDG. Accordingly, FDG activity is predicted to be determined by the number of bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these two latter factors can be effectively overcome by a proper distention of bowel segments through the administration of great amount of fluids, as in the case of PET/CT enterography[1,3,7,20,21]. To reduce the number of false positive findings in the intestinal tract during a PET scan, Franquet et al[22] proposed to undertake a therapy with Rifaximine 2 d before the PET scan. In their paper, this patient preparation allowed to reduce the unspecific FDG uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, false positive cases due to physiologic uptake of the radiopharmaceutical in normal bowel can be often found in clinical practice. However, false positive findings can be effectively reduced with a proper distention of bowel segments through the administration of great amount of fluids[1,3,7,20,21] or by specific patients preparations as reported by Franquet et al[22]. …”
Section: Discussionmentioning
confidence: 99%